Lived Experiences of Learners With Cerebral Palsy Educated in Inclusive Classrooms in the Czech Republic - Sedláčková, Dagmar; Kantor, Jiří (Frontiers in Education, 2022)
Abstract Changes in legislation in the Czech Republic in 2016 moved the system of education towards inclusion and created more favorable conditions for joint education, but we still do not have enough information about experiences of learners with cerebral palsy educated in an inclusive environment. A qualitative design was chosen to explore the lived experiences of Czech learners with cerebral palsy educated in inclusive schools. Semi-structured interviews combined with biographical narration of learners with cerebral palsy, aged 12 - 20, and a brief questionnaire for demographic data were used for data collection. Data analyses were carried out according to van Manen’s approach, including defining the main themes and description of the lived experiences of learners. The following four themes were identified: (1) barriers, (2) strategies for overcoming obstacles, (3) values in relation to peers, (4) and the future. The results of this qualitative study point to a number of obstacles and pressures that these pupils face in their education, as well as to the ways of solving some problems. The results indicate that it is important to realize that the consequences of interpersonal relationships significantly influence the formation of self-concept and personality development of these students, and therefore it is necessary for teaching staff to deal with the support of positive relationships at schools. When creating a supportive inclusive environment, it is also necessary to pay attention to the pupils’ future, because the present Czech society does not offer sufficiently inclusive conditions in further education and occupation.